MORAL SELF-PERCEPTION OF ADOLESCENTS (Annual of the Faculty of Philosophy in Skopje, 2012)
This research examines differences in moral self-perception of adolescents with different age, gender, type of behavior and family. The total number of participants is 260, where 92 are girls and 168 are boys. The average age of participants from early adolescence is 14.5 years, from middle adolescence is 17.7 years, while the average age of participants from late adolescence is 21.4 years. All participants are Macedonians, with Orthodox religion.The results indicate that older adolescents, adolescents who do not manifest asocial or antisocial behavior and adolescents who live with their parents who are in marriage are choosing moral values and virtues as more central and more important to their moral self-perception compared to younger adolescents, and to their peers who manifest asocial or antisocial behavior and those who live in institutions for children without parents and parental care. No differences are registered according to gender of adolescents.
Keywords: MORAL SELF-PERCEPTION; MORAL VALUES AND VIRTUES; ADOLESCENCE; ASOCIAL AND ANTISOCIAL BEHAVIOR